Differential kinetics of response and toxicity using stereotactic radiation and interventional radiological coiling for pulmonary arterio‐venous shunting from metastatic leiomyosarcoma. Issue 4 (23rd April 2015) - Wong, Annie Ngai Man; Siva, Shankar; Manser, Renee; Dowling, Richard; Antippa, Phillip; Chin, Kwang; Mileshkin, Linda Rose
Summary Case report demonstrating the differential kinetics of response and toxicity using stereotactic radiation and interventional radiological coiling for pulmonary arterio‐venous shunting from leiomyosarcoma pulmonary metastases.